Laser fragmentation of amorphous and crystalline selenium of various morphologies and assessment of their antioxidant and protection properties - Simakin, Alexander V.; Baimler, Ilya V.; Dikovskaya, Anastasia O.; Kazantseva, Dina V.; Yanykin, Denis V.; Voronov, Valery V.; Uvarov, Oleg V.; Astashev, Maxim E.; Sarimov, Ruslan M.; Ivanov, Vladimir E.; Bruskov, Vadim I.; Kozlov, Valeriy A. (Frontiers in Chemistry, 2024)
The process of laser-induced breakdown of amorphous and crystalline selenium nanoparticles (Se NPs) of various shapes during nanosecond laser fragmentation of aqueous colloidal solutions of nanoparticles with different concentrations has been studied. It has been established that in the process of laser fragmentation of selenium nanoparticles at a wavelength of 532 nm, corresponding to the maximum absorption of selenium, the highest probability of breakdown, the number of plasma flashes, their luminosity and the amplitude of acoustic signals are achieved at concentrations of the order of 10 9 NPs/ml. It has been shown that the use of selenium nanoparticles of various shapes and structures leads to a change in the photoacoustic signal during laser-induced breakdown. When crystalline selenium nanoparticles are irradiated, the intensity of the photoacoustic response during breakdown turns out to be greater (1.5 times for flash luminosity and 3 times for acoustics) than when amorphous particles are irradiated at the same concentration. It has been shown that selenium nanoparticles exhibit significant antioxidant properties. Selenium nanoparticles effectively prevent the formation of reactive oxygen species (ROS) during water radiolysis, eliminate radiation-induced active forms of proteins, and reduce the radiation-chemical yield of a key marker of oxidative DNA damage -8-oxoguanine. In general, the antioxidant properties are more pronounced in amorphous selenium nanoparticles compared to crystalline selenium nanoparticles.